2014
DOI: 10.4314/tjpr.v13i7.10
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of (-)-Epigallocatechin Gallate against Photo-Damage Induced by Ultraviolet A in Human Skin Fibroblasts

Abstract: Purpose: To investigate the photoprotective effect of (-)-epigallocatechin gallate (EGCG), one of tea catechins, on human skin fibroblast (HSF) irradiated by ultraviolet A. Methods: HSF cells were incubated in serum-free Dulbecco's Modified Eagle's Medium (DMEM) with or without EGCG for 2 h, and then irradiated by UV A. Blank (control) was incubated in DMEM without EGCG and UV A-irradiation. Cell viability was determined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) method. Protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Cytoprotective effects of GSE on human gingival fibroblasts from several oxidative stressors were previously reported and thought to be independent of its direct antioxidant action 24 . Contrary to these findings, it was shown that major catechin of green tea, epigallocatechin gallate (EGCG), improved the viability of dermal fibroblasts exposed to UVA along with the inhibition of UV‐induced generation of oxidative stressors including superoxide anion radicals, lipid peroxidation, and malondialdehyde (MDA) and suppression of glutathione peroxidase (GSH‐Px) activity 25 . In addition, the topical treatment of human epidermal keratinocytes with grape seed proanthocyanidins (GSPs) was able to inhibit lipid and protein oxidation, and support the skin's own antioxidant system associated with the reduction in UV‐induced oxidative damage 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Cytoprotective effects of GSE on human gingival fibroblasts from several oxidative stressors were previously reported and thought to be independent of its direct antioxidant action 24 . Contrary to these findings, it was shown that major catechin of green tea, epigallocatechin gallate (EGCG), improved the viability of dermal fibroblasts exposed to UVA along with the inhibition of UV‐induced generation of oxidative stressors including superoxide anion radicals, lipid peroxidation, and malondialdehyde (MDA) and suppression of glutathione peroxidase (GSH‐Px) activity 25 . In addition, the topical treatment of human epidermal keratinocytes with grape seed proanthocyanidins (GSPs) was able to inhibit lipid and protein oxidation, and support the skin's own antioxidant system associated with the reduction in UV‐induced oxidative damage 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Inulavosin might compete with the copper chaperon and inhibit the copper loading processing in living melanocytes [15]. Green tea EGCG is a benzoderivative with 8 hydroxyl groups, which has strong antioxidant activity [8,16]. It is deduced that the melanogenesis inhibitory effect of EGCG may be related to its abundant hydroxyl groups and its antioxidant activity.…”
Section: Discussionmentioning
confidence: 98%
“…EGCG protects human skin fibroblasts from photo-damage induced by UVA [8] and reduces melanin synthesis via reduction of the protein levels of MITF [9,10]. The present study set to investigate the effect of EGCG on TRY activity and melanogenesis in UV A induced B16 murine melanoma cell lines.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Perubahan radikal peroksil melalui reaksi siklisasi menjadi endoperoksida yang pada akhirnya akan menghasilkan MDA. 31 Senyawa MDA merupakan produk peroksidasi lipid yang paling mutagenik dan digunakan sebagai biomarker peroksidasi lipid asam lemak omega-3 serta omega-6 karena kemudahannya bereaksi dengan thiobarbituric acid (TBA). 32 Akumulasi MDA di dalam sel dapat mengakibatkan terjadinya degradasi seluler, perubahan biokimia dan fungsional, bahkan kematian sel.…”
Section: Spirulina Platensisunclassified